The Model of Cooperative Supervision Institution as an Effort of Legal Protection for the Public: Model Lembaga Pengawasan Koperasi Sebagai Upaya Perlindungan Hukum Bagi Masyarakat - Teguh Rizkiawan (Universitas Islam Indonesia, 2023)
This research aims to determine and analyze the problems of the existing Koperasi’s supervision arrangements and the model of Koperasi’s supervision institutions as an effort to protect society in the future. This research is normative-juridical research that uses a statutory approach and a conceptual approach to analyze the formulation of the problem under study. The results of this research conclude that Law Number 25 of 1992 on Koperasi is no longer relevant for carrying out the supervisory function of koperasi(s) nowadays. Based on Law Number 25 of 1992, the government does not have the authority to supervise koperasi(s). This then becomes a loophole that financial criminals exploit to operate. This is then supported by the many cases of Savings and Loans Koperasi failure to pay, causing both material and immaterial losses to the community. Through the reformulation of Law Number 25 of 1992, the government can adopt two models of the Koperasi’s supervision institutions, namely the Financial Services Authority as a cooperative supervisory institution and the establishment of a new institution, the Koperasi Supervisory Authority.Keywords: Koperasi, Supervisory Institutions, and Legal Protection. AbstrakPenelitian ini bertujuan untuk mengetahui dan menganalisis problematika pengaturan pengawasan koperasi yang berlaku dan model lembaga pengawasan koperasi sebagai upaya perlindungan hukum bagi masyarakat ke depannya. Penelitian ini merupakan penelitian yuridis normatif yang menggunakan pendekatan perundang-undangan dan pendekatan konseptual untuk menganalisis rumusan masalah yang diteliti. Hasil penelitian ini menyimpulkan bahwa Undang-Undang Nomor 25 Tahun 1992 tentang Perkoperasian sudah tidak relevan guna melakukan fungsi pengawasan koperasi saat ini. Dalam UU Nomor 25 Tahun 1992, pemerintah tidak memiliki kewenangan untuk mengawasi koperasi. Hal ini yang kemudian menjadi celah yang dimanfaatkan pelaku kejahatan keuangan untuk beroperasi. Hal tersebut kemudian didukung dengan banyaknya kasus-kasus KSP yang gagal bayar sehingga menimbulkan kerugian baik secara materil maupun immaterial kepada masyarakat. Melalui reformulasi UU Nomor 25 Tahun 1992, pemerintah dapat mengadopsi dua model lembaga pengawasan koperasi, yaitu Otoritas Jasa Keuangan sebagai lembaga pengawas koperasi dan pembentukan lembaga baru, Otoritas Pengawas Koperasi. Kata Kunci: Koperasi, Lembaga Pengawas, dan Perlindungan Hukum.